The Chance of Permanent Cure for Micro- and Macroprolactinomas, Medication or Surgery? A Systematic Review and Meta-Analysis - Ma, Qianquan; Su, Jun; Li, Ying; Wang, Jiaxing; Long, Wenyong; Luo, Mei; Liu, Qing (Frontiers in Endocrinology, 2018)
Background: This meta-analysis aims to evaluate the long-term efficacy of medication treatment versus surgery treatment in patients with prolactinomas. Methods: An electronic literature search was performed using MEDLINE, EMBASE and Web of Science databases for studies dated before July in 2018. Patients with prolactinomas received primary dopamine agonists (DAs) treatment or primary surgical interventions were included in this study. A systematic review and meta-analysis were performed in pertinent studies meeting eligible criteria. The clinical outcome was measured by the long-term remission rate of prolactin (PRL) in each cohort. The pooled data was analyzed according to a random effect model. Results: Thirteen publications with total 809 patients were included in the final meta-analysis. In the overall patients with prolactinomas, long-term remission rate was achieved in 88% patients treated with surgeries and in 52% patients treated with DAs (P=0.001). The long-term remission rates in surgery cohort were also significantly higher than medication cohort in both microprolactinomas and macroprolactinomas (91% versus 60%, P=0.002; 77% versus 43%, P=0.003). Conclusions: Patients with prolactinomas, especially microprolactinomas, can consider transsphenoidal surgery as an alternative first-line treatment strategy. After receiving primary surgical intervention, administration of DAs should be considered based on the postoperative PRL level to achieve the best long-term remission rate.